The Small GTPase Rab7 Regulates Antigen Processing in B Cells in a Possible Interplay with Autophagy Machinery - Runsala Marika; Kuokkanen Elina; Uski Eveliina; Šuštar Vid; Balci Meryem Özge; Rajala Johanna; Paavola Vilma; Mattila Pieta K (MDPI, 2025)
In B cells, antigen processing and peptide-antigen (pAg) presentation is essential to ignite high-affinity antibody responses with the help of cognate T cells. B cells efficiently internalize and direct specific antigens for processing and loading onto MHCII. This critical step, which enables pAg presentation, occurs in MHCII compartments (MIICs) which possess the enzymatic machinery for pAg loading on MHCII. The intracellular transport systems that guide antigen and maintain this unique compartment remain enigmatic. Here, we probed the possible functional role of two known endosomal proteins, the Rab family small GTPases Rab7 and Rab9, that are both reported to colocalize with internalized antigen. As compared to Rab9, we found Rab7 to exhibit a higher overlap with antigen and MIIC components. Rab7 also showed a higher association with antigen degradation. The inhibition of Rab7 drastically decreased pAg presentation. Additionally, we detected the strong colocalization of perinuclearly clustered and presumably MIIC-associated antigen with autophagy protein LC3. When we pharmacologically inhibited autophagy, pAg presentation was inhibited. Together, our data promote Rab7 as an important regulator of antigen processing and, considering the previously reported functions of Rab7 in autophagy, this also raises the possibility of the involvement of autophagy-related machinery in this process.